NEGOTIATING TRADITION AND INNOVATION UPON THE CROSS-GENERATIONAL ART OF SINGIRAN (IMPROVISATION, CULTURAL IDENTITY AND MILLENNIAL COMMUNITY) - Sobirin, Mohamad (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2019)
This study, based on recent virtual observation, explores the process of cultural negotiations of singing Singiran among millennial. In addition, it also breaks down the strategies practiced by the Singiran musicians in introducing their artistic products into digital society. In this study, in addition to observing the lyrics and chords of Singiran, I interviewed Rijal Vertizon and his associates; the musicians who have popularity based on the number of their subscribers. The Singiran musicians regenerated the tradition of singing Singiran with innovation, especially upon the arrangement of the music, as well as developing a strategy to improve sounds and fulfill the aesthetic changes of populist Muslim markets and newly emerging millennial Muslim identities. In addition to reconstructing this traditional culture, Singiran musicians are interested in creating a positive image both for insiders and outsiders of Javanese cultures and reaching the larger Muslim community. My observations to the Singiran's enthusiasts show that innovative Singiran can play a role in shaping the cultural identity of the Javanese Millennial Muslim. In other perspective, it could be called as a new kind of local wisdom in contemporary Javanese life.